Fund for food: a campus food pantry toolkit to help fight hunger on campus / Nurul Hafizah Mohd Yasin ... [et al.] - Mohd Yasin, Nurul Hafizah; Nordin, Nurhaiza; Nordin, Nurnaddia; Nik Mud, Nik Noorhazila; Mat Zaib, Siti Zamanira (2021)
Inadequate financial resources have led to food insecurity among students at higher institutions due to the increase in study fees, house rental costs, and food prices. As such, the increased living standards and price of goods are among the factors influencing food insecurity among university students. In fact, hunger and food insecurity are evident in this day and age, even on college campuses. Since college meal plan for students is especially too expensive for low-income students to bear, some students are forced to engage in part-time jobs to earn extra income for food and other expenses. This also includes living on a shoestring budget as college education becomes less affordable for university students. In view of these problems, campuses have recently established food pantries to help students. However, running a campus food pantry requires careful planning and a dedicated team of leaders and volunteers; hence, this study aims to provide a food pantry toolkit as a guideline to solve hunger and food insecurity among university students by setting up food pantries on campus to provide food and other essentials to the students in need. Depending on the campus, this program is run by the student government, other student organizations, or administrative departments such as the Office of Student Affairs. The food pantry toolkit should comprise the following facets: i) demonstrating the need for food pantries on campus by surveying the university students, faculty, and staff members; ii) community partnership through a fiscal sponsor and potential groups or companies as community partners; iii) setting up of space, equipment, and storage depending on the type of food to be distributed; and iv) food safety procedures via training and safe food handling provided to the volunteers. Considering the new-developed toolkit to fight hunger on campus as the innovation novelty of this study, universities in Malaysia are, therefore, expected to become a driving force in improving food insecurity by implementing the On-Campus Food Pantry Program to help ease student hunger.